Retirement savings adequacy in U.S. defined contribution plans - Francisco J. Gomes; Kenton Hoyem; Wei-yin Hu; Enrichetta Ravina (Federal Reserve Bank of Chicago, 2022)
We evaluate retirement savings adequacy using a large panel of U.S. workers with a 401(k) account. We model medical expenditures, longevity, investment risk, and the likelihood of withdrawals due to hardship, job separation, and reaching age 59 1/2. Based on their current account balances, income, saving, and investment behavior, three in four workers in our sample are not saving enough for retirement. The dispersion is related to plan features, account balances, but also worker saving behavior. A bequest motive, lower housing equity, higher risk aversion, lower discount rates or lower future returns worsen the shortfall. We examine various counterfactual policy interventions.
Keywords: 330; Altersvorsorge; Arbeiter; Sparen; Privater Konsum; Lebensverlauf; USA